Draft Annual Plan 1990-91 in the Context of 8th Five Year Plan 1990-1995 Government of Mizoram - Planning Commission (Planning Commission, 1990)
Mizoram occupies a, very strategic position in the North Eastern corner of India having an International boundary of 710 Kms and covers an are of 21,087 Sq. Kms. The Tropic of Cancer runs through the State of Mizoram. It is bounded on the North by the States of Assam and Manipur, on the East and South by Chin Hills of Burma and on the West by Chitagong Hill Tracts in Bangladesh and the State of Tripura. It is linked with State of Assam on the North of the State.
Planning and Programme Implementation Department, Government of Mizoram